Observational study of medical marijuana as a treatment for treatment‐resistant epilepsies. Issue 4 (10th March 2022) - Devinsky, Orrin; Marmanillo, Angelica; Hamlin, Theresa; Wilken, Philip; Ryan, Daniel; Anderson, Conor; Friedman, Daniel; Todd, George
Abstract: Objectives: Medical cannabis formulations with cannabidiol (CBD) and delta‐9‐tetrahydrocannabinol (THC) are widely used to treat epilepsy. We studied the safety and efficacy of two formulations. Methods: We prospectively observed 29 subjects (12 to 46 years old) with treatment‐resistant epilepsies (11 Lennox–Gastaut syndrome; 15 with focal or multifocal epilepsy; three generalized epilepsy) were treated with medical cannabis (1THC:20CBD and/or 1THC:50CBD; maximum of 6 mg THC/day) for ≥24 weeks. The primary outcome was change in convulsive seizure frequency from the pre‐treatment baseline to the stable optimal dose phase. Results: There were no significant differences during treatment on stable maximal doses for convulsive seizure frequency, seizure duration, postictal duration, or use of rescue medications compared to baseline. No benefits were seen for behavioral disorders or sleep duration; there was a trend for more frequent bowel movements compared to baseline. Ten adverse events occurred in 6/29 patients, all were transient and most unrelated to study medication. No serious adverse events were related to study medication. Interpretation: Our prospective observational study of two high‐CBD/low‐THC formulations found no evidence of efficacy in reducing seizures, seizure duration, postictal duration, or rescue medication use. Behavioral disorders or sleep duration was unchanged. Study medication was generally well tolerated. The doses of CBD used were lower than prior studies. Randomized trials with larger cohorts are needed, but we found no evidence of efficacy for two CBD:THC products in treating epilepsy, sleep, or behavior in our population.